The N- or C-terminal cytoplasmic regions of P4-ATPases determine their cellular localization - Okamoto, Sayuri (2021)
Mammalian P4-ATPases specifically localize to the plasma membrane and the membranes of intracellular compartments. P4-ATPases contain 10 transmembrane domains, and their N- and C-terminal (NT and CT) regions face the cytoplasm. Among the ATP10 and ATP11 proteins of P4-ATPases, ATP10A, ATP10D, ATP11A, and ATP11C localize to the plasma membrane, while ATP10B and ATP11B localize to late endosomes and early/recycling endosomes, respectively. We previously showed that the NT region of ATP9B is critical for its localization to the Golgi apparatus, while the CT regions of ATP11C isoforms are critical for Ca2+-dependent endocytosis or polarized localization at the plasma membrane. Here, we conducted a comprehensive analysis of chimeric proteins and found that the NT region of ATP10 proteins and the CT region of ATP11 proteins are responsible for their specific subcellular localization. Importantly, the ATP10B NT and the ATP11B CT regions were found to harbor a trafficking and/or targeting signal that allows these P4-ATPases to localize to late endosomes and early/recycling endosomes, respectively. Moreover, dileucine residues in the NT region of ATP10B were required for its trafficking to endosomal compartments. These results suggest that the NT and CT sequences of P4-ATPases play a key role in their intracellular trafficking.